(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the intelligent quotient between Night Owls and Morning Larks chronotypes in medical students of LUMHS Jamshoro Karachi. Study Design: Descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the Department of Physiology and Pediatrics, Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro from November 2015 to October 2016. Materials and Methods: 225 MBBS students altogether including 120 males and 105 females via Simple Random Sampling from first year with age group (18-20). The student profiles were unspecified. Stanford Binnet Intelligence Scale was used for the IQ. To determine the chronotypes, Lark and Owl questionnaire was used which has 19 questions related to the circadian rhythm and one’s best feeling time. 1st year MBBS undergraduates belonging to the group of ages (18-20) were covered. Second year to final year MBBS students, Post-graduate students, house officers and those who were suffering from any major neurological or psychological illness were excluded. All the data was interpreted, Pearson’s chi square test was applied and results were drawn with the help of SPSS version 22 which is the statistical package of social sciences. Results: Among the extremely morning types out of 31 students in total, 10 (32.5%) were found to be genius, 3(9.6%) were had very superior IQ, 12(38.7%) were found to be superior and 5(16.1%) were average as shown in Table 2. In the moderately morning type category (n=12), 5 (41.6%) were found to be genius, 2(16.6%) had very superior IQ and 2(16.6%) were average. Among neutral types (n=87), 40 (45.9%) were found to be genius, 24(27.5%) were had very superior IQ, 15(17.2%) were found to be superior and 1(1.14%) were average. Moderately evening types (n=52) were found to have 8 (15.3%) genius, 22(42.3%) were had very superior IQ and 21(40.3%) were found to be superior. Among extremely evening type (n=43), 26(60.4%) were found to be genius, 7(16.3%) were had very superior IQ, 8(18.6%) were found to be superior and 1(2.3%) were average. The evening types were seemed to have higher IQ than morning type. Conclusion: 21st century is advancing so much in psychology that it’s important to know various dimensions of our own physiology that might improve the quality of our lives. In the light of previous literature and adding to this sparse data, this study showed that the medical students are more of evening types and that Eveningness has a positive correlation with intelligence.